Evolving conceptions of work-family boundaries: In defense of the family as stakeholder - Cunha, M. P. e; Hernández-Linares, R.; Sousa, M. de; Clegg, S.; Rego, J. (Humanistic Management Journal, 2022)
In the management and organization studies literature, a key question to explore and explain is that of the family as an organizational stakeholder, particularly when working-from-home became the “new normal”. Departing from meta-analytic studies on the work-family relation and connecting with scholarly conversation on work-family boundary dynamics, we identify three main narratives. In the separation narrative, work and family belong to different realms, and including the family in the domain of organizational responsibility is seen as pointless. The interdependence narrative stresses that organizations and families are overlapping domains in which it is important to acknowledge that the policies and practices of the former might have an impact on family life, and vice-versa. The embeddedness narrative, brought to the fore by the COVID-19 pandemic, sees employment and family as progressively convergent and hybrid work domains. The evolution of employment relations towards increased hybridity of the work situation being embedded in the familial/household context increasingly calls for consideration of the family/household as an integral rather than a peripheral stakeholder.